PEMENUHAN KEBUTUHAN AKAN KELEKATAN PADA ANAK DALAM KONTEKS BUDAYA BENGKULU - Maya, Dian Mustika; Zumkasri, Zumkasri (Faculty of Psychology, Diponegoro University, 2017)
This qualitative study aims to explore how mothers fulfill the need for attachment on their children in the context of Bengkulu culture. The study participants comprised five mothers that were identified using purposive sampling method. The following characteristics were applied: 1) the third generation of a family that lived in Bengkulu, 2) the nuclear family lives together, 3) she has a child with a minimum of 2 years of age, and 4) she uses local language to communicate within the family. The data analysis resulted in the following 10 themes or categories: 1) The use of local language to respond to the child’s need for attachment; 2) The attached figure (mother) used an insecure attachment; 3) Mother responds spontaneously depends on the situation; 4) The tone of mother’s voice affects the child’s perception; 5) The mother’s emotion influences her chosen words; 6) The intrinsic factors that affect the fulfillment of child’s attachment were marriage readiness, the quality of marriage relationship, and verbal ability; 7) The extrinsic factors affect the fulfillment of child’s need for attachment were financial condition, the environment where the participants lived, and education level; 8) Treating a child as an object; 9) The structure of extended family reinforces child’s insecure attachment; 10) Interaction pattern and character of the society.